Adaptation of Temperate Seagrass to Arctic Light Relies on Seasonal Acclimatization of Carbon Capture and Metabolism - Jueterbock, Alexander; Duarte, Bernardo; Coyer, James; Olsen, Jeanine L.; Kopp, Martina Elisabeth Luise; Smolina, Irina; Arnaud-Haond, Sophie; Hu, Zi-Min; Hoarau, Galice (Frontiers in Plant Science, 2021)
Due to rising global surface temperatures, Arctic habitats are becoming thermally suitable for temperate species. Whether a temperate species can immigrate into an ice-free Arctic depends on its ability to tolerate extreme seasonal fluctuations in daylength. Thus, understanding adaptations to polar light conditions can improve the realism of models predicting poleward range expansions in response to climate change. Plant adaptations to polar light have rarely been studied and remain unknown in seagrasses. If these ecosystem engineers can migrate polewards, seagrasses will enrich biodiversity and carbon capture potential in shallow coastal regions of the Arctic. Eelgrass (Zostera marina) is the most widely distributed seagrass in the northern hemisphere. As the only seagrass species growing as far north as 70°N, it is the most likely candidate to first immigrate into an ice-free Arctic. Here, we describe seasonal (and diurnal) changes in photosynthetic characteristics, and in genome-wide gene expression patterns under strong annual fluctuations of daylength. We compared PAM measurements and RNA-seq data between two populations at the longest and shortest day of the year: 1) a Mediterranean population exposed to moderate annual fluctuations of 10-14 hours daylength, and 2) an Arctic population exposed to high annual fluctuations of 0-24 hours daylength. Most of the gene expression specificities of the Arctic population were found in functions of the organelles (chloroplast and mitochondrion). In winter, Arctic eelgrass conserves energy by repressing respiration and reducing photosynthetic energy fluxes. Although light-reactions, and genes involved in carbon capture and carbon storage were up-regulated in summer, enzymes involved in CO2 fixation and chlorophyll-synthesis were up-regulated in winter, suggesting that winter metabolism relies not only on stored energy resources, but also on active use of dim light conditions. Eelgrass is unable to use the excessive amounts of light during summer and demonstrates a significant reduction in photosynthetic performance under long daylengths, possibly to prevent photoinhibition constrains. Our study identified key mechanisms that allow eelgrass to survive under Arctic light conditions, and paves the way for experimental research to predict whether and up to which latitude eelgrass can potentially migrate polewards in response to climate change.